The Level of Skills of Mini Volleyball Bottom Service of 4th Grade Students of Public Elementary School 13 Bengkulu Tengah Year 2023/2024 - Berli, Franse; Perdima , Feby Elra; Asnawati (Universitas Dehasen Bengkulu, 2024)
This study aims to determine the skill level of mini volleyball underhand serve skills of fourth grade students of SD Negeri 13 Central Bengkulu for the 2023/2024 academic year. This type of research is descriptive quantitative using survey methods and data collection technique used were tests and measurements. The results of this study were based on the underhand serve skill test of which was categorized very high, namely 2 people (8%), high category namely 3 people (12%), and moderate category namely 13 people (52%), and the low category was 7 people (28%), and the very low category was 0 people (0%). Based on the results above, it can be concluded that the underhand serve skills of fourth grade students of SD Negeri 13 Central Bengkulu in the academic year of 2023/2024, the results of the underhand serve test were obtained with an average of 12.6 and were in the moderate category.